Ekstrak Buah Lerak (Sapindus rarak) sebagai Sabun Antibakteri yang Ramah Lingkungan - Novitarini, Novitarini; Kresnapati, I Nyoman Bagus Aji; Akmi, Alfarizi Muzaifa (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2024)
Synthetic surfactants contribute to environmental pollution and can cause skin irritation, highlighting the need for natural biosurfactants. Lerak fruit (Sapindus rarak) shows promise as a biosurfactant due to its 28% saponin content and potential antibacterial activity. This study aimed to evaluate the antibacterial activity of lerak fruit extract using three parameters: inhibition zone, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) against Staphylococcus aureus (Gram-positive) and Pseudomonas aeruginosa (Gram-negative). The research utilized a Posttest Only Control Group Design to test the antibacterial activity of lerak fruit extract against skin-surface normal flora, specifically Staphylococcus aureus and Pseudomonas aeruginosa. All antibacterial activity results were analyzed using One-Way ANOVA in SPSS IBM version 22. The study found the MIC to be 6.25% for Gram-positive bacteria and 1.56% for Gram-negative bacteria. The MBC was determined to be 25% for Gram-positive bacteria and 50% for Gram-negative bacteria. At a 50% concentration, the inhibition zones against Gram-positive and Gram-negative bacteria were 21.53 mm and 22.13 mm, respectively. These results demonstrate that lerak fruit extract possesses strong antibacterial activity against both Gram-positive and Gram-negative bacteria. This research provides a foundation for developing environmentally friendly antibacterial soap formulations using lerak fruit extract.